Produksi Video Microlearning di UPT SD Negeri 067098 Medan - Triadi Sya’Dian; Muhammad Ali Mursid Alfatoni; Tamama Alvin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to produce a microlearning video product that can help teachers understand and learn good and correct teaching methods. Microlearning videos are chosen because of their ability to convey material concisely and effectively, making it easier for teachers to receive information quickly and accurately. The research method used is research and development (R&D) with a qualitative approach. The video production process includes several stages, namely material planning, scripting, shooting, video editing, and product evaluation. This research was conducted at UPT SD Negeri 067098 Medan. Based on the evaluation results, the resulting video was considered good and suitable for use for learning purposes. The results of the study indicate that the microlearning video produced can be an effective tool for teachers in understanding the concept of correct teaching methods. In addition, this video can also help improve the teaching skills of teachers at UPT SD Negeri 067098 Medan, as well as provide clear guidance in implementing effective teaching methods in the classroom.